PENERAPAN STRATEGI COLLABORATIVE LEARNING PADA MATA PELAJARAN IPS TERPADU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII DI SMP IT ULIL ALBAB BATAM TAHUN PELAJARAN 2015/2016 STRATEGY IMPLEMENTATION OF COLLABORATIVE LEARNING ON THE SUBJECT IN THE INTEGRATED IPS IMPROVING STUDENT LEARNING MOTIVATION CLASS VII SMP IT IN BATAM ULIL albab LESSON YEAR 2015/2016 - Desma Yulia; Devi Liana Sari (CAHAYA PENDIDIKAN, 2016)
Teacher-centered learning less than optimal impact on the lack of student motivation. In addition, students are also difficult to understand the learning material of teaching materials that have been provided so that students become less enthusiastic in receiving lessons. This study aims to reveal the students 'motivation on IPS Terpadu  subjects through CollaborativeLearning strategy and to know the of the differences in students' motivation Experimental Class and ControlClass in junior IT UlilAlbab Batam. This research is a quantitative research with Quasi-Experimental Design approach. The subjects were students of class VIIa as a Class Experiment, totaling 32 students and Class VIIb as a Class control totaling 32 students. The sampling is using random sampel.Data obtained from the test results questionnaire were analyzed using the average difference test (T-Test). The results of this study indicate that there are significant differences on the students motivation in the Experimental Class Kata kunci: Strategi Collaborative Learning, students motivation, social sciences. Berpusat pada guru belajar kurang dari dampak yang optimal pada kurangnya motivasi siswa. Selain itu, siswa juga sulit untuk memahami materi pembelajaran bahan ajar yang telah disediakan sehingga siswa menjadi kurang antusias dalam menerima pelajaran. Penelitian ini bertujuan untuk mengungkapkan motivasi pada mata pelajaran IPS Terpadu melalui strategi CollaborativeLearning dan untuk mengetahui perbedaan di siswa siswa motivasi Kelas Eksperimental dan ControlClass di SMP IT UlilAlbab Batam. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan Desain Quasi-Eksperimental. Subjek penelitian ini adalah siswa kelas VIIA sebagai Eksperimen Kelas, berjumlah 32 siswa dan kelas VIIB sebagai kontrol Kelas berjumlah 32 siswa. sampling menggunakan sampel.Data acak yang diperoleh dari hasil uji kuesioner yang dianalisis menggunakan uji perbedaan rata-rata (T-Test). Hasil penelitian ini menunjukkan bahwa terdapat perbedaan yang signifikan pada motivasi siswa di Kelas Eksperimental dan Kontrol.Kata kunci: Strategi Collaborative Learning, Motivasi Belajar, IPS Terpadu.